KAJIAN PENGARUH PENGUKUSAN BERTEKANAN (STEAM PRESSURE TREATMENT) TERHADAP SIFAT FISIKOKIMIA TEPUNG JAGUNG [Study of The Effects of Steam Pressure Treatment on The Physicochemical Properties of Corn Flour] - Siti Khomsatin; . Sugiyono; Bambang Haryanto (Jurnal Teknologi dan Industri Pangan, 2012)
The objectives of this research were to study the effects of steam pressure treatments on the physicochemical properties of corn flour and to apply the corn flour for cookies production. The research was conducted in three stages. The first stage was the production of corn flour through wet milling process. The second stage was the analysis of physicochemical properties of corn flours receiving steam pressure treatment for 10, 20, 30, 40, 50 and 60 minutes. The third stage was the production of cookies using the pre-treated corn flour. Thermal properties evaluation of the corn flour showed that gelatinization temperatures (To, Tp, Tc) and gelatinization degrees (DG) increased but gelatinization enthalpy (ΔH) and temperature range (R) decreased as the time for steam pressure treatment increased. The rheological properties showed that maximum viscosity (PV), hot paste viscosity (HPV), breakdown viscosity (BV), cold paste viscosity (CPV) and setback viscosity (SV) of pre-treated corn flour decreased as the steam pressure treatment time increased. The steam pressure treatment changed the gelatinization profile from B to C type. Correlation analyses showed that the PV had positive correlation with swelling volume. The PV, HPV, BV, CPV and SV had negative correlation with the DG. The swelling volume and water solubility of the pre-treated corn flour were significantly affected by the steam pressure time. The swelling volume decreased but the water solubility increased. The steam pressure treatment did not give significant effects to water absorption capacity (WAC), amylose, amylopectin and moisture content of corn flour. The DG had positive correlation with the water solubility and the WAC but it had negative correlation with the swelling volume. The water solubility had negative correlation with the ΔH. Application of the pre-treated corn flour for cookies production reduced sandiness of cookies.